2017
DOI: 10.1186/s13059-017-1186-2
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic aging signatures in mice livers are slowed by dwarfism, calorie restriction and rapamycin treatment

Abstract: BackgroundGlobal but predictable changes impact the DNA methylome as we age, acting as a type of molecular clock. This clock can be hastened by conditions that decrease lifespan, raising the question of whether it can also be slowed, for example, by conditions that increase lifespan. Mice are particularly appealing organisms for studies of mammalian aging; however, epigenetic clocks have thus far been formulated only in humans.ResultsWe first examined whether mice and humans experience similar patterns of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
296
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(310 citation statements)
references
References 50 publications
12
296
0
2
Order By: Relevance
“…Previous studies revealed increased entropy in human DNA methylation (Hannum et al., 2013) and in mouse livers aged 0.2 to 7.1 months old (Wang et al., 2017). We were able to examine changes in entropy across the whole mouse and human lifespan at a high resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed increased entropy in human DNA methylation (Hannum et al., 2013) and in mouse livers aged 0.2 to 7.1 months old (Wang et al., 2017). We were able to examine changes in entropy across the whole mouse and human lifespan at a high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mouse studies revealed age‐related changes in promoters and increasing methylation of development‐ and differentiation‐related pathways (Maegawa et al., 2010). A global age‐related increase in entropy was also shown (Wang et al., 2017), and dietary restriction was found to influence hepatic genes involved in lipid metabolism‐related pathways (Hahn et al., 2017). Another advantage of mouse studies is that they allow investigating evolutionarily conserved and species‐specific changes during aging and examining the effects of interventions that extend lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…For genomic features, this often takes the form of determining if changes are more or less likely than chance to occur in a certain feature such as a promoter, intron, and CG island. A number of examples exist from recent studies (Cole et al 2017;Dozmorov 2017;Hadad et al 2017b;Masser et al 2017a;Wang et al 2017). For integration with other epigenomic data, the process is similar but the comparison is with other epigenomic data such as ChIP-Seq.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…DNA methylation profiles have even been used to define an “epigenetic clock” (Horvath, 2013; Stubbs et al, 2017b). Epigenetic alterations associated with aging have been found to be accelerated or slowed as a result of high fat diet and caloric restriction, respectively (Cole et al, 2017; Stubbs et al, 2017b; Wang et al, 2017). Recent work profiling transcription in livers of mice found that, while protein coding genes can be activated or repressed with no particular bias in one direction or the other, non-coding RNAs (sRNAs and lncRNAs) and transposable elements were largely activated and this trend could be reversed by lifespan extending interventions such as caloric restriction (Green et al, 2017).…”
Section: Epigenetics and Environmental Influencesmentioning
confidence: 99%